AKIBAT HUKUM KELALAIAN KREDITUR DALAM MELAKUKAN ROYA ATAS JAMINAN FIDUSIA - Ninik Meiyudianti (Fakultas Hukum Universitas Islam Indragiri, 2018)
Obligation of creditor in making report for nullification of debt in fiduciary registration office to delete the record of fiduciary object is known as liability omission (Roya). Liability omission can be done when debtor paying off all debts that is possessed to the creditor. When liability omission (roya) is not conducted by the creditor after debtor pay off all the debt, it certainly harms the debtor since he/she as debtor is not able to use the fiduciary object to make new credit agreement with other parties. The present research aims to elaborate and examine further about the obligation of creditor in performing liability omission toward the fiduciary object when the debtor paying off all the debts. Moreover, the present study tries to elaborate further about accountability of creditor regarding negligence in performing liability omission toward fiduciary object that has been paid off. The method used in the present study is a normative legal research, namely legal research which is conducted by examining the library materials or secondary law while in finding and collecting the data is done by two approaches, namely the law and conceptual approaches. The present study shows that deletion record of fiduciary object based on paying off of debts by the debtor shall be performed by the creditor. When creditor neglects in performing this act within fourteen days (14) after the repayment of debt, it can be justified as infringement of law. Moreover, creditor shall responsible to pay all losses that is experienced by the debtor.